PENGARUH PELATIHAN CONTINUOUS CIRCUIT TERHADAP PENINGKATAN KECEPATAN DAN KELINCAHAN - Agus Sumanadi, I Komang (Jurnal Ilmu Keolahragaan Undiksha, 2013)
This research aimed at knowing the effect of continuous circuit training toward speed and agility of basketball extracurricular students in SMA Negeri 4 Singaraja which consisted of 24 students. The subject of the research was divided into two groups by using ordinal pairing technique. The type research used in this study was quasi experimental which used the modification non-randomized control group pre-test post-test design as the design of the study. The speed was measured by using sprint test 60 meters and the agility was measured by using zig-zag run, and then the data was analyzed by using t-independent test at 5% alpha level of significance by the used of SPSS program. The result of the data analysis of the speed showed that the significance value of speed = 0.003 and the significance value of agility = 0.000. Those results showed that the significance values of speed and agility was lower than Î± = 0,05 so that the hypothesis was accepted. Based on the results of data analysis and the explanation above, it can be concluded that continuous circuit training gave effect on increasing the speed of basketball extracurricular students in SMA Negeri 4 Singaraja in which the significance was lower than 0.01 and the continuous circuit training also gave effect on increasing the agility of basketball extracurricular students in SMA Negeri 4 Singaraja in which the significance was lower than 0.01. It is suggested to use this training as an alternative in increasing speed and agility.